Bone marrow biopsy diagnostic yield in internal medicine. Issue 1 (2nd January 2021) - Martellosio, Jean-Philippe; Puyade, Mathieu; Debiais, Céline; Elsendoorn, Antoine; Souchaud-Debouverie, Odile; Landron, Cédric; Luca, Luminita; Roy-Peaud, Frédérique; Milin, Serge; Roblot, Pascal; Martin, Mickaël
ABSTRACT: Background: Trephine bone marrow biopsy (BMB) in internal medicine has only been studied in fever of unknown origin and inflammation of unknown origin. The aim was to assess BMB diagnostic yield according to main indications and patient characteristics in internal medicine. Quality of BMB and contribution of bone marrow aspiration (BMA) to BMB were also analyzed. Methods: BMB performed in the internal medicine department of Poitiers university hospital between January 2000 and December 2015 were retrospectively analyzed. Patient characteristics, BMB indications, quality parameters, and results were collected from medical records. Contributive BMB was BMB allowing accurate final diagnosis. Diagnostic yield was the proportion of contributive BMB among total BMB performed. Results: A total of 468 BMBs conducted for primary diagnostic purpose from 468 patients were analyzed. Cytopenia(s) and the indication 'adenopathy and/or splenomegaly and/or hepatomegaly' represented 70% of the indications. Overall BMB diagnostic yield was 32.7%, lymphoma being the main histologic finding (31%). Among indications, cytopenia(s) had the highest diagnostic yield (49.1%). Isolated fever of unknown origin had low diagnostic yield (5.6%). Factors independently associated with contributive BMB were: anemia, neutropenia, circulating immature granulocytes or blasts, monoclonal gammopathy, period of BMB processing, quality of BMB, and immunohistochemestry (IHC) analysis. Concomitant BMA improved diagnostic yield by 5.5%, mostly for myelodysplastic syndromes. Conclusion: Cytopenia(s), blood cythemias and monoclonal gammopathy are indications with the highest diagnostic yield. Concomitant BMA and IHC analysis should be systematically performed to increase BMB diagnostic yield in internal medicine.